Intraoperative measurement of bowel oxygen saturation using a multispectral imaging laparoscope - Clancy,NT; Arya,S; Stoyanov,D; Singh,M; Hanna,GB; Elson,DS (Biomedical Optics Express, 2015)
Intraoperative monitoring of tissue oxygen saturation (StO2) has potentially important applications in procedures such as organ transplantation or colorectal surgery, where successful reperfusion affects the viability and integrity of repaired tissues. In this paper a liquid crystal tuneable filter-based multispectral imaging (MSI) laparoscope is described. Motion-induced image misalignments are reduced, using feature-based registration, before regression of the tissue reflectance spectra to calculate relative quantities of oxy- and deoxyhaemoglobin. The laparoscope was validated in vivo, during porcine abdominal surgery, by making parallel MSI and blood gas measurements of the small bowel vasculature. Ischaemic conditions were induced by local occlusion of the mesenteric arcade and monitored using the system. The MSI laparoscope was capable of measuring StO2 over a wide range (30-100%) with a temporal error of ± 7.5%. The imager showed sensitivity to spatial changes in StO2 during dynamic local occlusions, as well as tracking the recovery of tissues post-occlusion.